APLIKASI LISTENING PEMBELAJARAN BAHASA INGGRIS PADA MAHASISWA AKUNTANSI SEMESTER IV POLITEKNIK NEGERI BALI - Putu Dyah Hudiananingsih (Soshum: Jurnal Sosial dan Humaniora, 2013)
Some time it is difficult to attract the students’ interest in learning English. One of the reasons why they are not interested in learning this language is because they are boring. To avoid this situation happen, the students are invited to work in multi media room. They are asked to listen to the tape and play asking and answering questions. By doing this kind of activity, it is hoped that the students will be eager enough to practice their English which have been learnt for long time. As it is said by Erlinda R. Boyle from Chinese University of Hong Kong in Forum Magazine Volume 31 Number 3 July 1993 page 36 as follow: “The ideal environment for improving in a second language is one where the target language is spoken and heard all the time”. From what it is mentioned above, it is known that the best way to learn foreign language is: live where that language is spoken.. According to Jeremy Harmer ( 2001:229) the advantage of learning English through listening tape is : “taped material allow students to hear variety of different voices apart from just their own teacher’s. It gives them opportunity to ‘meet’ a range of different characters”. This means that it is much better when we ask our students listen to the tape repeatedly, so they will be familiar with different character of voice. This influence their ability in comprehending what the people said.